(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article presents the main assignment of English borrowings for lexical system of publicistic texts. In spite of some positive sides the harmfulness of English borrowings is presented in their excessive or inappropriate using which can be followed by displacement of Ukrainian vocabulary. This process is better seen in the publicistic texts.